Nitric Oxide- and Heme-Independent activation of soluble guanylate cyclase attenuates peroxynitrite-induced endothelial dysfunction in rat aorta - Korkmaz-İçöz, Sevil; Loganathan, Sivakkanan; Mikles, Beatrice; Barnucz, Enikő; Hirschberg, Kristóf; Li, Shiliang; Hegedűs, Péter; Páli, Szabolcs; Weymann, Alexander; Karck, Matthias; Szabó, Gábor (Journal of cardiovascular pharmacology and therapeutics, 2013)
Oxidative stress interferes with nitric oxide (NO)/soluble guanylate cyclase (sGC)/cyclic guanosine monophosphate (cGMP) signalling pathway through reduction of endogenous NO and formation of the strong intermediate oxidant peroxynitrite and leads to vascular dysfunction. We evaluated the effects of oral treatment with NO- and heme-independent sGC activator cinaciguat on peroxynitrite-induced vascular dysfunction in rat aorta. Sprague-Dawley rats were treated orally 2 times at an interval of 17 hours with vehicle or with cinaciguat (10 mg/kg). One hour after the last treatment, the animals were anesthetized, the thoracic aorta was removed, and the aortic segment preparations were incubated with and without the reactive oxidant peroxynitrite (200 µmol/L, 30 minutes). Endothelium-dependent (acetylcholine), -independent (sodium nitroprusside) vasorelaxations were investigated, and histopathological examination was performed. Incubation of aortic rings with peroxynitrite significantly attenuated the maximal endothelium-dependent relaxation (Rmax) to acetylcholine (peroxynitrite, 44.5% ± 5.9% vs control, 93.2% ± 2.0%, P < .05) and decreased pD2 values (-logEC50, EC50 being the concentration of acetylcholine that elicited 50% of the maximal response) for the concentration-response curves as compared to control segments. Treatment of rats with cinaciguat significantly improved the decreased acetylcholine-induced vasorelaxation after exposure of aortic rings to peroxynitrite (cinaciguat + peroxynitrite, 67.1% ± 3.5% vs peroxynitrite, 44.5% ± 5.9%, P < .05). Incubation of aortic segments with peroxynitrite caused a significant shift of the sodium nitroprusside concentration-response curves to the right without any alterations in the Rmax. Moreover, exposure of aortic rings to peroxynitrite resulted in increased nitro-oxidative stress and DNA breakage which were improved by cinaciguat. Treatment of rats with cinaciguat significantly increased intracellular cGMP levels in the aortic wall. Our results show under conditions of nitro-oxidative stress when signalling in the NO/sGC/cGMP pathway is impaired, acute activation of sGC by cinaciguat might be advantageous in the treatment of endothelial dysfunction in cardiovascular disease.
Gesehen am 20.11.2018
Article first published online: August 22, 2012